Adenocarcinoma of the anal canal: A report of two cases with review of literature - Medha Pradip Kulkarni; Yasmin Altaf Momin; Amitkumar Bapuso Pandav; Kalpana Ranjitsingh Sulhyan (Wolters Kluwer Medknow Publications, 2016)
Adenocarcinoma of the anal canal accounts for about 20% of all anal canal cancers. It is subclassified into two types. (1) Colorectal type, which arises from the mucosa above dentate line and (2) extramucosal type, which includes adenocarcinoma arising in anorectal fistulae and adenocarcinoma arising from anal glands. Anal gland adenocarcinomas are extremely rare. In this article, we present two cases of anal adenocarcinoma, one colorectal type, and other anal gland carcinoma along with review of literature.